IMPLEMENTASI PENGELOLAAN PENDIDIKAN FORMAL DAN INFORMAL MELALUI KEGIATAN PEMBELAJARAN SERTA PELAKSANAAN PROSES PELAYANAN ADMINISTRASI DAN PELAYANAN PUBLIK - Partiwi, Marsha Hijro; Putra, Eka; Bustami, Yuserizal (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
This research aims to increase understanding of what the true definition of management itself is and to understand the scope of Islamic education management as well as the boundaries of objects that are targets or goals for managers of Islamic education institutions. The method used is a qualitative approach through case studies. The data collection techniques used are 1) Documentation 2) Interviews 3) Observation. The results of this research show that many people and youth in Nagari Talang Koto Pulai, Alam Ampek Hulu Tapan District, South Coast District do not fully understand the meaning or definition of management and the scope of management of Islamic education in schools and in society.